G223 Higher percentage of insulin pump users achievable by a small team! experience of paediatric diabetes team at isle of man (iom). (12th March 2018) - Gangadharan, A; Unsworth, P; Varshney, V; Kurien, A
Abstract : Introduction: Continuous subcutaneous Insulin infusion (CSII) using pump has revolutionised the management of diabetes in children. Studies have demonstrated that better metabolic control could be achieved using insulin pump. NICE recommends use of insulin pump in children with poor metabolic control, disabling hypoglycaemia or clinical situations where MDI use is not practical. National Paediatric Diabetes Audit (NPDA) reports serves as yardstick to compare individual unit performance against wider national data. The IOM, not part of NPDA cohort aims to provide highest quality of care by critically analysing its performances against national audit outcomes. Aims: To assess the prevalence of pump users and mean HbA1c on the Island Compare unit performance with NPDA report Identify the potential ways of promoting wider insulin pump use in T1D Methodology: Data of all diabetic patients from April 2015- March 2016 managed at Nobles hospital, IOM. Key outcomes such as age, percentage of pumps users, mean HbA1c, and prevalence of associated disorders was collected. All results were compared to NPDA report for the year 2015–2016. Results [Combined England and Wales data in bold] Total of 48 patients with T1D [M=25 (52%)] with a median age of 13.2 years (range 6.2–19.0) at the final point of data collection. The mean HbA1c was 63.3 mmol/mol [68.3], <58 mmol/mol was 31.2% [26.6%] and >80 mmol/mol was 6.2% [17.9%] . A total of 90% (43/48, 27-Animas, 15-Omnipod and 1-Medtronic who moved from UK) were on pump compared to 28 % in England and Wales for the same period. Rest of them were on MDI. Associated coeliac disease (1) and thyroid disorder (1) was noted. There were 3 admissions of hyperglycaemia/ketosis during this period. Conclusions: Better glycaemic control is achieved in a smaller unit in spite of a very high percentage of pump users. Provision of only 2 different pumps helped in better utilisation of expertise and at the same time providing crucial choice for the users (tube Vs tubeless). Though part funding from charity organisation helps in procuring the pumps, it does not guarantee long term sustainability and hence need for liberal funding options by NHS.